Responsabilidade social na FUCAPI: visão atual e perspectivas - Eliana Migliorin da Rosa (2004)
The depth of involvement of an organization with the issue of social responsibility can be studied by using a hierarchical model (MONTANA & CHARNOV, 1998). At its most primitive stage, an organization only fulfills its legal obligations whereas, if it is at the most advanced stage, it also adopts a proactive attitude, where it commits itself to solving socialproblems, even though only indirectly affected by them. The Centre for Analysis, Research and Technological Innovation Foundation (FUCAPI) is the subject of this case study. In order to investigate what type of approach FUCAPI has taken towards social issues in its socialactivities, its managers and employees were interviewed and their responses were compared with institutional documents. FUCAPIs approach to social responsability was analysed by using Montana & Charnovs (1998) theoretical model and recommendations were made so that the organization could become more effective and proactive in its social actions.